2019
DOI: 10.1186/s12885-019-6107-1
|View full text |Cite
|
Sign up to set email alerts
|

Real-world experience of first-line afatinib in patients with EGFR-mutant advanced NSCLC: a multicenter observational study

Abstract: Background This study aimed to evaluate the efficacy, side-effects and resistance mechanisms of first-line afatinib in a real-world setting. Methods This is a multicenter observational study of first-line afatinib in Malaysian patients with epidermal growth factor receptor (EGFR)-mutant advanced non-small cell lung cancer (NSCLC). Patients’ demographic, clinical and treatment data, as well as resistance mechanisms to afatinib were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 33 publications
5
30
1
Order By: Relevance
“…In LUX-Lung 7 and LUX-Lung 8 studies, it was found that patients treated with afatinib as both first-line treatment (compared with gefitinib) and second-line treatment (compared with erlotinib) resulted in a longer PFS or OS[ 10 , 11 ]. However, most patients with rare or complex EGFR mutations had a shorter PFS than patients with exon 19 deletion (16.0 mo vs 9.0 mo; HR, 0.34; 95%CI, 0.13-0.94, P = 0.037)[ 12 ]. In addition, it has been reported that patients aged ≥ 65 years with rare mutations have significantly longer PFS than patients aged < 65 years after receiving EGFR TKIs (median PFS: 10.5 mo vs 5.5 mo, P = 0.0320)[ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In LUX-Lung 7 and LUX-Lung 8 studies, it was found that patients treated with afatinib as both first-line treatment (compared with gefitinib) and second-line treatment (compared with erlotinib) resulted in a longer PFS or OS[ 10 , 11 ]. However, most patients with rare or complex EGFR mutations had a shorter PFS than patients with exon 19 deletion (16.0 mo vs 9.0 mo; HR, 0.34; 95%CI, 0.13-0.94, P = 0.037)[ 12 ]. In addition, it has been reported that patients aged ≥ 65 years with rare mutations have significantly longer PFS than patients aged < 65 years after receiving EGFR TKIs (median PFS: 10.5 mo vs 5.5 mo, P = 0.0320)[ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the time of this study (2015)(2016)(2017), guidelines recommended first-line (1L) treatment of EGFRm advanced NSCLC with first-or second-generation (1G/2G) EGFR-tyrosine kinase inhibitors (TKIs) erlotinib, gefitinib or afatinib [10][11]. Despite initial efficacy, most patients with EGFRm advanced or metastatic NSCLC treated with a 1L 1G/2G EGFR-TKI develop resistance, with disease progression occurring after a median of 8 to 16 months [12][13][14]. The EGFR T790M acquired resistance mutation has been observed in approximately 50% of patients from a meta-analysis of clinical trials [15] while rates of approximately 30% have been reported in real-world studies [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The AURA-3 clinical trial demonstrated that second-line osimertinib had signi cantly greater e cacy than pemetrexed plus platinum-based therapy in advanced-stage T790M-mutated NSCLC during treatment with rst-line EGFR TKIs such as ge tinib, erlotinib, and afatinib 7 . AURA-3 reported 10.1 months of PFS on osimertinib and 4.4 months of adjustment on survival outcomes in patients with EGFR-mutated NSCLC reported that patients who received dose reductions experienced higher ORRs 19 . Another RWD study showed that dose adjustment reduced the number and intensity of several side effects, emphasizing that tailored dose modi cation could help treatment optimization and improve survival outcomes 20 .…”
Section: Discussionmentioning
confidence: 99%